2018
DOI: 10.1002/ece3.3952
|View full text |Cite
|
Sign up to set email alerts
|

High midday temperature stress has stronger effects on biomass than on photosynthesis: A mesocosm experiment on four tropical seagrass species

Abstract: The effect of repeated midday temperature stress on the photosynthetic performance and biomass production of seagrass was studied in a mesocosm setup with four common tropical species, including Thalassia hemprichii, Cymodocea serrulata, Enhalus acoroides, and Thalassodendron ciliatum. To mimic natural conditions during low tides, the plants were exposed to temperature spikes of different maximal temperatures, that is, ambient (29–33°C), 34, 36, 40, and 45°C, during three midday hours for seven consecutive day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 58 publications
5
44
1
Order By: Relevance
“…The stress responses recorded upon the plants were similar in magnitude to a previous study on the same species (George et al, ), but with a slightly stronger influence at 40°C, as indicated in the ETR and Fv/Fm levels. The negative effects of high midday temperature stress on the photosynthetic performance were intensified by the number of repeated days of exposure, indicating chronic damage in the photosynthetic machinery as the maximum quantum yield (Fv/Fm) could not recover even after several hours of darkness and ambient temperatures (Beer, Björk, & Beardall, ; Hanelt, ; Maxwell & Johnson, ).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The stress responses recorded upon the plants were similar in magnitude to a previous study on the same species (George et al, ), but with a slightly stronger influence at 40°C, as indicated in the ETR and Fv/Fm levels. The negative effects of high midday temperature stress on the photosynthetic performance were intensified by the number of repeated days of exposure, indicating chronic damage in the photosynthetic machinery as the maximum quantum yield (Fv/Fm) could not recover even after several hours of darkness and ambient temperatures (Beer, Björk, & Beardall, ; Hanelt, ; Maxwell & Johnson, ).…”
Section: Discussionsupporting
confidence: 82%
“…The loss of photosynthetic capacity, and a subsequent decrease in the internal O 2 transport to below‐ground tissues, has been shown to cause anoxia in seagrass sediments (Greve, Borum, & Pedersen, ; Nagel, ), and a decrease in photosynthetic capacity (by shading) of tropical seagrasses has been suggested to have a negative effect on the part of the microbial community of seagrass sediment using photosynthetically produced exudates from the seagrass (Barber & Carlson, ; Schrameyer et al, ). Such effects might have shifted the microbial activity to cause an additional increase in sulfate reduction and methanogenesis, causing the increase in sulfide levels and methane emissions observed in this study, possibly also strengthened by the decay of below‐ground tissues, which has been observed under events of elevated midday temperature stress (George et al, ) and suggested to be a source of the organic matter supporting sediment CH 4 production in seagrass meadows (Barber & Carlson, ). As expected, any changes in the microbial activity and composition did, however, not result in any significant change in the organic matter content of the sediment.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…, George et al. ). The shading caused by the storm event in the experiment would have direct negative effects on the amount of oxygen produced in the leaves of the seagrass, thus reducing the amount of oxygen transported from the leaves to the roots.…”
Section: Discussionmentioning
confidence: 99%